Article having coating film, composition, and method for producing article having coating film
Patent Information
- Application Number
- JP2024123656
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2024-03-28
- Filing Date
- 2024-07-30
- Publication Date
- 2025-02-13
AI Technical Summary
【0011】 本発明の一態様によれば、幅広い波長域の光線(紫外線および高エネルギー可視光線)を遮光し得る酸化亜鉛含有被膜を有する物品を提供することが可能になる。
Smart Images

Figure 2025021461000009 
Figure 2025021461000010 
Figure 2025021461000011
Abstract
Description
[Technical field]
[0001] The present invention relates to articles having a coating, compositions and methods for making articles having a coating. [Background technology]
[0002] Patent documents 1 to 5 and non-patent documents 1 and 2 disclose zinc oxide-containing coatings and methods for producing the same. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-147695 A [Patent Document 2] JP 2014-205811 A [Patent Document 3] Japanese Patent Application Publication No. 7-182939 [Patent Document 4] Patent No. 5288464 specification [Patent Document 5] JP 2019-152702 A [Non-patent literature]
[0004] [Non-Patent Document 1] Japan Society for the Promotion of Science, Committee 166 on Transparent Oxide High-Electronic Materials, Technical Revision 2nd Edition of Transparent Conductive Films (2006) [Non-Patent Document 2] K. Sorab, et al. Appl. Phys. Lett., 37(5), 1 September 1980 Summary of the Invention [Problem to be solved by the invention]
[0005] Zinc oxide-containing coatings are used in a wide range of fields due to their transparency and heat resistance. Furthermore, in recent years, the ultraviolet ray shielding function of zinc oxide-containing coatings has attracted attention. For example, Patent Document 1 discloses a glass container that has a high visible light transmittance and an ultraviolet ray shielding function achieved by coating the outer surface with a zinc oxide-containing coating. Patent Document 1 also describes that, regarding the heat resistance that is a characteristic of zinc oxide-containing coatings, no change in transmittance, etc. was observed even after long-term exposure to high temperatures of 300°C or higher (see paragraph 0048 of Patent Document 1).
[0006] Various methods are known for forming a zinc oxide-containing coating (see Non-Patent Document 1). Specific examples of the method for forming a zinc oxide-containing coating include a method of forming the zinc oxide-containing coating by a vacuum film formation method such as sputtering, a method of forming the zinc oxide-containing coating as a coating containing an organic or inorganic binder and zinc oxide particles (see Patent Document 2), a chemical vapor deposition (CVD) method (see Non-Patent Document 2), a spin coating method, a spray pyrolysis method (see Patent Documents 3 to 5), and the like.
[0007] Regarding coatings provided on various articles, in various applications including pharmaceutical applications involving biopharmaceuticals and other light-sensitive pharmaceuticals, there is a demand for coatings that can block ultraviolet rays and also block short-wavelength visible light (high-energy visible light), which has the second highest energy after ultraviolet rays.
[0008] Regarding the light-shielding function of zinc oxide-containing coating, it is theoretically difficult to block light rays of 380 nm or more with the band gap derived from zinc oxide. Therefore, in recent years, it has been studied to aim at expanding the light-shielding wavelength range by adding other metal components to the zinc component. For example, Patent Document 6 describes that when a zinc oxide-containing coating doped with a foreign metal was produced using a composition containing dialkyl zinc and a foreign metal precursor (organometallic compound), the zinc oxide-containing coating had an improved UV-A (315 nm to 380 nm) light-shielding rate while maintaining good transparency (see Examples in Patent Document 6). However, in the Examples in Patent Document 6, the shift of the absorption edge achieved by doping with a foreign metal was only 376 nm (see Table 2 in Patent Document 6), and there is still room for improvement in the light-shielding ability to block light rays in the longer wavelength range.
[0009] An object of one aspect of the present invention is to provide an article having a zinc oxide-containing coating capable of blocking light rays in a wide wavelength range (ultraviolet rays and high-energy visible light). [Means for solving the problem]
[0010] One aspect of the present invention is as follows. [1] An article having a coating film on a substrate that satisfies the following (1) to (4): (1) In the grayscale image of a cross-sectional STEM (Scanning Transmission Electron Microscope), a layered structure in which low-brightness regions and high-brightness regions are alternately stacked is confirmed. (2) Oxygen, zinc, and iron were detected in cross-sectional observations using STEM-EDX (Scanning Transmission Electron Microscope-Energy Dispersive X-ray Spectroscopy). (3) In cross-sectional observation by STEM-EDX, the EDX intensity ratio of iron to zinc (Zn / Fe) in the region observed as the low brightness region is higher than the EDX intensity ratio (Zn / Fe) in the region observed as the high brightness region. (4) The percentage of the iron atoms relative to the total of the zinc atoms and iron atoms contained in the coating is more than 0.4 atomic %. [2] The article according to [1], wherein the film thickness of the low-luminance region is in the range of 5.0 nm or more and 250.0 nm or less, and the film thickness of the high-luminance region is in the range of 5.0 nm or more and 250.0 nm or less. [3] The article according to [1] or [2], wherein in the laminated structure, the total number of layers in the low-luminance region is 1 to 15 layers, and the total number of layers in the high-luminance region is 1 to 15 layers. [4] The article according to any one of [1] to [3], wherein in the laminated structure, the total number of layers in the low-luminance region is 1 to 15 layers, and the total number of layers in the high-luminance region is 1 to 15 layers. [5] The transmittance characteristics of the above coating are: The average transmittance in the wavelength range of 600 nm to 800 nm is 75.0% or more, The transmittance at a wavelength of 350 nm is 6.0% or less, and The article according to any one of [1] to [4], which has a transmittance of 80.0% or less at a wavelength of 420 nm. [6] The film thickness of the low-brightness region is in the range of 5.0 nm to 250.0 nm, The film thickness of the high brightness region is 5.0 nm or more and 250.0 nm or less, In the laminated structure, the total number of layers in the low-luminance region is 1 to 15 layers, and the total number of layers in the high-luminance region is 1 to 15 layers, The transmittance characteristics of the coating are: The average transmittance in the wavelength range of 600 nm to 800 nm is 75.0% or more, The transmittance at a wavelength of 350 nm is 6.0% or less, and The article according to any one of [1] to [5], which has a transmittance of 80.0% or less at a wavelength of 420 nm. [7] The article described in [6], wherein in the laminated structure, the total number of layers in the low-luminance region is 1 to 15 layers, and the total number of layers in the high-luminance region is 1 to 15 layers. [8] Formula (1): Formula (1): R 1 -Zn-R2 (In formula (1), R 1 and R 2 each independently represents a linear or branched alkyl group having 1 to 8 carbon atoms. and an organozinc compound represented by the formula: The following formula (2): [ka] (In formula (2), R 3 and R 4 each independently represents a linear or branched alkyl group having 1 to 8 carbon atoms. and a β-diketone metal compound represented by the formula: and A composition in which the content of the β-diketone metal compound is greater than 10 atomic %, expressed as a percentage of the iron atoms relative to the total of the zinc atoms contained in the organozinc compound and the iron atoms contained in the β-diketone metal compound. [9] In formula (2), R 3 and R 4 and each of the groups represents a methyl group.
[10] The composition described in [8] or [9], wherein the content of the β-diketone metal compound is, as a percentage of the iron atoms relative to the total of the zinc atoms contained in the organozinc compound and the iron atoms contained in the β-diketone metal compound, more than 10 atomic % and not more than 80 atomic %.
[11] The composition according to any one of [8] to
[10] , further comprising an organic solvent.
[12] The composition according to
[11] , wherein the organic solvent is one or more organic solvents selected from the group consisting of aromatic hydrocarbon solvents and aromatic electron-donating solvents.
[13] In formula (2), R 3 and R 4 Each of these represents a methyl group. the content of the β-diketone metal compound is, as a percentage of the iron atoms to the total of the zinc atoms contained in the organozinc compound and the iron atoms contained in the β-diketone metal compound, more than 10 atomic % and not more than 80 atomic %; The composition according to any one of [8] to
[12] , further comprising one or more organic solvents selected from the group consisting of aromatic hydrocarbon solvents and aromatic electron-donating solvents.
[14] A method for producing an article having a coating on a substrate, the method comprising applying the composition according to any one of [8] to
[13] onto the substrate. Effect of the Invention
[0011] According to one aspect of the present invention, it is possible to provide an article having a zinc oxide-containing coating capable of blocking light rays in a wide wavelength range (ultraviolet rays and high-energy visible light rays). [Brief description of the drawings]
[0012] [Figure 1] 1 shows the transmission spectrum of the coating formed in Example 1. [Diagram 2] 1 shows the transmission spectrum of the coating formed in Example 2. [Diagram 3] 1 shows the transmission spectrum of the coating formed in Example 3. [Figure 4] 1 shows the transmission spectrum of the coating formed in Example 4. [Diagram 5] 1 shows the transmission spectrum of the coating formed in Example 5. [Figure 6] 1 shows the transmission spectrum of the coating formed in Example 6. [Figure 7] 1 shows the transmission spectrum of the coating formed in Comparative Example 1. [Figure 8] 1 shows the transmission spectrum of the coating formed in Comparative Example 2. [Figure 9] 1 shows the transmission spectrum of the coating formed in Comparative Example 3. [Figure 10] 1 shows the transmission spectrum of the coating formed in Comparative Example 4. [Figure 11] 1 is a graph in which the results of quantitative analysis of the iron content of the coatings formed in Comparative Example 1, Comparative Example 4, Example 1, Example 2, and Example 4 are plotted against the percentage of iron atoms in the coating liquid (coating composition). [Figure 12]1 shows a grayscale image (256 gradations) and brightness analysis results of a cross-sectional STEM image of a randomly selected portion of the coating formed in Example 6 across the entire thickness direction. [Figure 13] 1 shows the results of cross-sectional observation by STEM-EDX and the results of EDX intensity analysis of a randomly selected portion of the coating formed in Example 6 over the entire thickness direction. [Figure 14] This shows the film thickness and the total number of layers for low and high brightness regions in a grayscale image (256 gradations) of a cross-sectional STEM image of a randomly selected portion of the coating formed in Example 6 across the entire thickness direction. [Figure 15] 1 shows a grayscale image (256 gradations) and brightness analysis results of a cross-sectional STEM image of a randomly selected portion of the coating formed in Example 1 across the entire thickness direction. [Figure 16] 1 shows the results of cross-sectional observation by STEM-EDX and the results of EDX intensity analysis of a randomly selected portion of the coating formed in Example 1 over the entire thickness direction. [Figure 17] This shows the film thickness and the total number of layers for low and high brightness regions in a grayscale image (256 gradations) of a cross-sectional STEM image of a randomly selected portion of the coating formed in Example 1 across the entire thickness direction. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] [Goods] One aspect of the present invention relates to an article having, on a substrate, a coating that satisfies the following (1) to (4). (1) In the grayscale cross-sectional STEM image, a layered structure in which low-brightness and high-brightness regions are alternately stacked is confirmed. (2) Oxygen, zinc, and iron are detected in cross-sectional observations using STEM-EDX. (3) In cross-sectional observation by STEM-EDX, the EDX intensity ratio of iron to zinc (Zn / Fe) in the region observed as the low brightness region is higher than the EDX intensity ratio (Zn / Fe) in the region observed as the high brightness region. (4) The percentage of the iron atoms relative to the total of the zinc atoms and iron atoms contained in the coating is more than 0.4 atomic %.
[0014] As a result of extensive research, the present inventors have newly discovered that a coating that satisfies the above (1) to (4) can block light rays in a wide wavelength range (ultraviolet rays and high-energy visible light rays). The present inventors speculate that the reason for this is as follows. Since the above coating satisfies the above (2), it is presumed to be a mixture film of zinc oxide and iron oxide. If the mixture film of multiple oxides is a homogeneous film in which the layered structure as in the above (1) is not observed, it is considered that the optical properties such as light blocking properties are predominantly exhibited by the components present in high concentrations. Therefore, if zinc oxide is present in high concentrations in such a homogeneous film, the optical properties of the zinc oxide will be predominant, and the optical properties of the coating will be close to those of a zinc oxide film, making it difficult to block light in a wide wavelength range (ultraviolet rays and high-energy visible light). In contrast, the coating satisfies both (2) and (3), and is therefore believed to have regions where zinc oxide is present in high concentration (low luminance regions) and regions where it is present in low concentration (high luminance regions). It is presumed that the low luminance regions exhibit the optical properties of zinc oxide predominantly, while the high luminance regions are less affected by the optical properties of zinc oxide and exhibit the optical properties of iron oxide, making it possible to block light in a wide wavelength range (ultraviolet rays and high-energy visible light). Furthermore, it is believed that the coating's satisfaction of (4) contributes to the optical properties of iron oxide being exhibited well. However, the above is merely speculation, and the present invention is not limited to the speculation described in this specification.
[0015] The above-mentioned article will be described in more detail below. Hereinafter, the above-mentioned (1) to (4) will be referred to as film properties (1) to (4). The film properties (1) to (3) are measured at randomly selected points on a cross section of the film to be measured at randomly selected positions.
[0016] The cross-sectional STEM images in the present invention and this specification are taken under the following observation conditions: As an apparatus for obtaining the cross-sectional STEM images and performing STEM-EDX analysis, for example, an apparatus described in the Examples section below can be used. Observation magnification: 100,000 times Accelerating voltage during observation: 20 kV
[0017] <Coating> (Membrane properties (1)) Satisfying the film physical property (1) means that the brightness ratio (high brightness MIN / low brightness MAX) is 1.6 or more, where the arithmetic average of the brightness values of the high brightness areas, which are areas observed brighter than adjacent areas in a 256-tone grayscale image (when the entire thickness direction of the coating is observed and multiple high brightness areas are identified, the arithmetic average of the area with the lowest arithmetic average of the brightness values) is taken as "high brightness MIN" and the arithmetic average of the brightness values of the low brightness areas, which are areas observed darker than adjacent areas (when the entire thickness direction of the coating is observed and multiple low brightness areas are identified, the arithmetic average of the area with the highest arithmetic average of the brightness values) is taken as "low brightness MAX". Such a brightness ratio is preferably 1.7 or more, and more preferably 1.8 or more, 1.9 or more, 2.0 or more, 2.1 or more, and 2.2 or more in that order. The brightness ratio may be, for example, 3.0 or less, 2.9 or less, 2.8 or less, 2.7 or less, 2.6 or less, 2.5 or less, or 2.4 or less, and may be greater than the range exemplified herein.
[0018] In the laminated structure, the film thickness of the low brightness region and the film thickness of the high brightness region are not particularly limited. The film thickness of the low brightness region can be, for example, in the range of 5.0 nm to 250.0 nm, 5.0 nm to 200.0 nm, 5.0 nm to 150.0 nm, or 5.0 nm to 100.0 nm. The film thickness of the high brightness region can be, for example, in the range of 5.0 nm to 250.0 nm, 5.0 nm to 200.0 nm, 5.0 nm to 150.0 nm, or 5.0 nm to 100.0 nm. The film thickness of each region can be determined at randomly selected points in the grayscale image of the cross-sectional STEM image.
[0019] In the laminated structure, the low brightness region and the high brightness region are alternately laminated, and one or more layers of high brightness region and one or more layers of low brightness region are included. In the laminated structure, the low brightness region and the high brightness region are adjacent to each other (in other words, adjacent to each other) and alternately exist. The total number of layers of the low brightness region and the total number of layers of the high brightness region in the laminated structure are not particularly limited. In the laminated structure, the total number of layers of the low brightness region can be one or two or more layers, and the total number of layers of the high brightness region can be one or two or more layers. The total number of layers of the low brightness region can be, for example, one layer or more and 15 layers or less, and can be five layers or more and 15 layers or less. In addition, the total number of layers of the high brightness region can be, for example, one layer or more and 15 layers or less, and can be five layers or more and 15 layers or less. The total number of layers of the low brightness region and the total number of layers of the high brightness region may be the same number or different numbers. In one embodiment, both the outermost layer of one side and the outermost layer of the other side of the laminated structure can be low brightness regions. In this case, if the total number of layers of the low brightness region is "N", the total number of layers of the low brightness region and the high brightness region constituting the laminated structure is "2N-1" layers. In another embodiment, both the outermost layer of one side of the laminated structure and the outermost layer of the other side of the laminated structure can be high brightness regions. In this case, if the total number of layers of the high brightness region is "N", the total number of layers of the low brightness region and the high brightness region constituting the laminated structure is "2N-1" layers. In another embodiment, one outermost layer of the laminated structure can be a low brightness region and the other outermost layer can be a high brightness region. In this case, if the total number of layers of the low brightness region is "N", the total number of layers of the high brightness region is also "N", and the total number of layers of the low brightness region and the high brightness region constituting the laminated structure is "2N" layers.
[0020] (Membrane properties (2)) Satisfying the film physical property (2) means that oxygen, zinc, and iron are detected in cross-sectional observation by STEM-EDX. The region for cross-sectional observation by STEM-EDX is a randomly selected region including the entire thickness direction of the cross section of the coating to be measured. In the EDX intensity spectrum of STEM-EDX (vertical axis: intensity, horizontal axis: distance (i.e., thickness)), the range of intensity levels indicating the presence of each element (i.e., intensity above the lower limit of detection) can be continuous over the entire thickness direction (excluding both end regions that may include measurement errors, etc.) in each spectrum of oxygen (O), zinc (Zn), and iron (Fe). EDX intensity analysis can be performed by line analysis.
[0021] (Membrane properties (3)) Satisfying the film characteristic (3) means that the EDX intensity ratio (Zn / Fe) of iron to zinc in a region observed as a low brightness region in cross-sectional observation by STEM-EDX is higher than the EDX intensity ratio (Zn / Fe) in a region observed as a high brightness region. The EDX intensity ratio (Zn / Fe) of each region is calculated as the ratio of the arithmetic mean of Zn intensity to the arithmetic mean (also simply written as "average") of Fe intensity in that region. If the EDX intensity ratio (Zn / Fe) in the low brightness region is the "EDX low brightness region" and the EDX intensity ratio (Zn / Fe) in the high brightness region is the "EDX high brightness region", the ratio "EDX low brightness region / EDX high brightness region" can be, for example, 1.5 to 20.0, 1.5 to 15.0, 1.5 to 10.0, 1.5 to 5.0, or 1.5 to 3.5. In calculating the above ratio, the "EDX low brightness region" is the EDX intensity ratio (Zn / Fe) in the region with the lowest EDX intensity ratio (Zn / Fe) when multiple low brightness regions are identified by observing the entire thickness direction of the coating, and the "EDX high brightness region" is the EDX intensity ratio (Zn / Fe) in the region with the highest EDX intensity ratio (Zn / Fe) when multiple high brightness regions are identified by observing the entire thickness direction of the coating.
[0022] (Membrane properties (4)) Satisfying the film physical property (4) means that the percentage of the iron atoms relative to the total of the zinc atoms and iron atoms contained in the film (hereinafter also referred to as "iron content") is more than 0.4 atomic %. The iron content of the film can be determined by ICP-AES (Inductively Coupled Plasma Atomic Emission Spectroscopy). From the viewpoint of further improving the light-shielding performance, the iron content of the film is preferably 0.5 atomic % or more, and more preferably 1.0 atomic % or more, 3.0 atomic % or more, 5.0 atomic % or more, 10.0 atomic % or more, 15.0 atomic % or more, and 20.0 atomic % in that order. On the other hand, from the viewpoint of improving the transparency of the film, the iron content of the film is preferably 80.0 atomic % or less, and more preferably 75.0 atomic % or less, 70.0 atomic % or less, 65.0 atomic % or less, 60.0 atomic % or less, 55.0 atomic % or less, and 50.0 atomic % or less in that order.
[0023] (Film thickness) The thickness of the coating can be appropriately adjusted according to the use of the article, and is not particularly limited. A thicker coating tends to exhibit a better light-shielding function. The thickness of the coating can be, for example, 50 nm or more, 100 nm or more, 150 nm or more, 200 nm or more, 250 nm or more, 300 nm or more, 350 nm or more, 400 nm or more, 450 nm or more, 500 nm or more, 550 nm or more, 600 nm or more, 650 nm or more, or 700 nm or more. In addition, from the viewpoint of the transparency of the coating, the thickness of the coating is preferably 10 μm or less, more preferably 5 μm or less, and even more preferably 1 μm or less. The thickness can be measured by a stylus-type surface shape measuring device. An example of the measuring device can be the measuring device described in the Examples section below.
[0024] (Light blocking function) An index of light-shielding function can be the transmittance measured at a wavelength in the ultraviolet region. The transmittance of the coating at various wavelengths can be measured by a commercially available spectrophotometer. The lower the transmittance at a measured wavelength, the better the function of blocking light at that measured wavelength. For example, the transmittance of the coating at a wavelength of 350 nm is preferably 6.0% or less, more preferably 5.0% or less, 4.0% or less, 3.0% or less, 2.0% or less, 1.0% or less, and 0.5% or less, and can be, for example, 0.0% or more, more than 0.0%, or 0.1% or more. An index of the light-shielding function can be the transmittance measured at the wavelength of high-energy visible light. For example, the transmittance of the coating at a wavelength of 420 nm is preferably 80.0% or less, more preferably 70.0% or less, 60.0% or less, 50.0% or less, 40.0% or less, 30.0% or less, and 20.0% or less, and can be, for example, 0.0% or more, more than 0.0%, 0.1% or more, 1.0% or more, 3.0% or more, or 5.0% or more. The present inventors speculate that the coating satisfying the film properties (1) to (4) contributes to the coating being able to exhibit an excellent light-shielding function against ultraviolet light with a wavelength of 350 nm, and further being able to exhibit an excellent light-shielding function against high-energy visible light with a wavelength of 420 nm, which is a longer wavelength.
[0025] (Visible light transmittance) A coating having high visible light transmittance and excellent transparency is useful in various fields. In one embodiment, the coating may be a coating having high visible light transmittance. The visible light transmittance of the coating can be 75.0% or more, preferably 78.0% or more, more preferably 80.0% or more, and even more preferably 85.0% or more, as an average transmittance in the visible light region of 600 nm to 800 nm. The visible light transmittance of the coating can be, for example, 99.0% or less, 95.0% or less, or 90.0% or less. The average transmittance in the visible light region of 600 nm to 800 nm can be measured and determined by a commercially available spectrophotometer.
[0026] <Base material> Examples of the substrate of the above-mentioned article include various articles for which a light-shielding function is desired. The material constituting the substrate is not particularly limited, and examples thereof include metal, metal oxide, glass, concrete, various plastics, paper, wood, etc., and may be a composite material containing one or more of these. The shape of the substrate may be a plate-like shape, a curved shape, or a three-dimensional shape such as a container shape. The substrate may have an uneven surface. An example of the substrate may be a container described below. For example, in the pharmaceutical field, it is desirable to block light rays in a wide wavelength range in order to maintain the quality of pharmaceuticals. Therefore, it is desirable for containers used for storing and / or distributing pharmaceuticals to have excellent light-blocking properties against light rays in a wide wavelength range. For example, the above coating is suitable as a coating for imparting a light-blocking function to the outer and / or inner surfaces of such containers (i.e., substrates). The above coating is also suitable as a coating for imparting a light-blocking function to the outer and / or inner surfaces of containers (i.e., substrates) used for storing and / or distributing cosmetics, foods, etc.
[0027] The article can have the coating on at least a portion of the substrate. The coating can be located, for example, as the outermost layer of the article at the location where the coating is provided. When the substrate has a front surface and a back surface, the article can have the coating on, for example, a portion or the entire surface of either or both of the front surface and the back surface. The coating may be provided on at least a portion or the entire surface of the side surface of the substrate. The substrate on which the coating is provided may be a substrate alone, or may be a substrate having one or more layers laminated thereon.
[0028] The above-mentioned article may be any article to which it is desired to impart a light-shielding function against light rays in a wide wavelength range. Specific examples of such articles include glass windows, lenses, building materials, containers, etc. Examples of containers include the containers described above.
[0029] [Composition] One aspect of the present invention relates to a composition comprising an organozinc compound represented by formula (1) and a β-diketone metal compound represented by formula (2), wherein the content of the β-diketone metal compound is more than 10 atomic % as a percentage of the iron atoms relative to the total of the zinc atoms contained in the organozinc compound and the iron atoms contained in the β-diketone metal compound.
[0030] The composition may be a coating composition. In the present invention and this specification, the term "coating composition" refers to a composition that is applied onto a substrate or the like to form a coating.
[0031] During the film-forming process using the above composition, the organozinc compound represented by formula (1) can generate zinc oxide by reacting with, for example, water in the air. Therefore, the above composition can form a coating containing zinc oxide. On the other hand, the present inventors believe that the β-diketone metal compound represented by formula (2) can generate iron oxide by reacting during the film-forming process using the above composition. Therefore, it is presumed that the coating formed using the above composition contains zinc oxide and iron oxide. Furthermore, the above composition is suitable as a coating composition for forming the above-mentioned coating.
[0032] The above composition will now be described in more detail.
[0033] <Organic zinc compounds> The organozinc compound is represented by the following formula (1). Formula (1): R 1 -Zn-R 2
[0034] Formula (1) will now be described in more detail.
[0035] In formula (1), R 1 and R 2R each independently represents a linear or branched alkyl group having 1 to 8 carbon atoms. The organozinc compound represented by formula (1) is a dialkylzinc. 1 and R 2 In one embodiment, each represents the same alkyl group, and in another embodiment, each represents a different alkyl group.
[0036] Specific examples of the alkyl group include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, a hexyl group, an isohexyl group, a sec-hexyl group, a tert-hexyl group, a 2-hexyl group, a heptyl group, a 2-ethylhexyl group, and an octyl group.
[0037] The organozinc compound represented by formula (1) preferably has an alkyl group having 1 to 3 carbon atoms as the alkyl group. Diethylzinc (i.e., R 1 and R 2 are more preferably ethyl groups.
[0038] The above-mentioned organozinc compounds can be synthesized by known methods, and are also available as commercial products.
[0039] <β-diketone metal compounds> The β-diketone metal compound is represented by the following formula (2).
[0040] [ka]
[0041] Formula (2) shows the structure of a β-diketone metal compound as a complex (iron complex). 3 and alkyl groups represented by R 4Depending on the alkyl group represented by the formula (2), tautomerization may occur to form a β-diketone metal compound having a different bond state between the oxygen atom and the iron atom. Such a β-diketone metal compound may be in the form of a salt compound represented by the following formula (2)-1. In the present invention and this specification, the β-diketone metal compound represented by formula (2) also includes the form in which it exists as such a salt compound. R in formula (2) 3 and R 4 is R in Eq. (2). 3 and R 4 is synonymous with.
[0042] [ka]
[0043] Formula (2) will be explained in more detail below.
[0044] In formula (2), R 3 and R 4 R each independently represents a linear or branched alkyl group having 1 to 8 carbon atoms. 3 and R 4 In one embodiment, R represents the same alkyl group, and in another embodiment, R represents different alkyl groups. 3 In one embodiment, each of the three R represents the same alkyl group, in another embodiment, each of the three R represents a different alkyl group, and in another embodiment, two of the R represent the same alkyl group and the remaining one represents a different alkyl group. 4 The same applies to.
[0045] Specific examples of the alkyl group include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, a hexyl group, an isohexyl group, a sec-hexyl group, a tert-hexyl group, a 2-hexyl group, a heptyl group, a 2-ethylhexyl group, and an octyl group.
[0046] The β-diketone metal compound represented by formula (2) preferably has an alkyl group having 1 to 3 carbon atoms as the alkyl group, and is easily available. 3 and R 4 More preferably, each of these is a methyl group.
[0047] Specific examples of the β-diketone metal compound represented by formula (2) include iron(III) acetylacetonate and tris(dipivaloylmethanato)iron(III).
[0048] The above-mentioned β-diketone metal compounds can be synthesized by known methods, and are also available as commercial products.
[0049] The composition contains one or more of the organic zinc compound and the β-diketone metal compound, and may further contain a solvent. Only one type of solvent may be used, or two or more types may be mixed in any ratio. The solvent is preferably an organic solvent, more preferably an aromatic organic solvent, and even more preferably one or more organic solvents selected from the group consisting of aromatic hydrocarbon solvents and aromatic electron donating solvents. Specific examples of aromatic hydrocarbon solvents include benzene, toluene, ethylbenzene, xylene, mesitylene, and cyclohexylbenzene. Specific examples of aromatic electron donating solvents include anisole.
[0050] The content of the organic zinc compound in the composition is preferably defined as a content expressed in mass% with the total amount of the composition being 100 mass% from the viewpoints of producing a coating having a sufficient thickness, producing a transparent coating having excellent visible light transmittance, pot life, and suppressing nozzle clogging due to solvent evaporation. In detail, the content of the organic zinc compound in the composition is preferably 15 mass% or less, more preferably 12 mass% or less, and further preferably 9 mass% or less, and 6 mass% or less, with the total amount of the composition being 100 mass%. In addition, the content is preferably 1 mass% or more, more preferably 2 mass% or more, and further preferably 3 mass% or more, for example. The content is preferably within the above range from the viewpoints of producing a coating having a sufficient thickness, producing a transparent coating having excellent visible light transmittance, pot life, and suppressing nozzle clogging due to solvent evaporation.
[0051] The content of the β-diketone metal compound in the composition is defined as the percentage of the iron group atoms relative to the total of the zinc atoms contained in the organozinc compound and the iron atoms contained in the β-diketone metal compound from the viewpoint of controlling the light-shielding function of the coating formed using the composition. From the viewpoint, the percentage is more than 10 atomic %, preferably 15 atomic % or more, more preferably 20 atomic % or more, 30 atomic % or more, 40 atomic % or more, 50 atomic % or more, and 60 atomic % or more in that order. From the viewpoint of increasing the transparency of the coating formed, the percentage is preferably 90 atomic % or less, more preferably 80 atomic % or less, and even more preferably 70 atomic % or less. By controlling the content of the β-diketone metal compound in the composition, a coating satisfying the above-mentioned film property (4) can be formed.
[0052] The composition may contain only the above-mentioned components, or may contain one or more known components in any proportion.
[0053] By using the above composition, a coating containing zinc oxide can be formed. The coating containing zinc oxide thus formed can exhibit an excellent light blocking function against light rays in a wide wavelength range.
[0054] [Method of manufacturing an article having a coating] One aspect of the present invention relates to a method for producing an article having a coating on a substrate, the method comprising applying the above-described composition onto the substrate.
[0055] According to the above-mentioned manufacturing method, a coating containing zinc oxide can be formed by hydrolysis of an organic zinc compound represented by formula (1) contained in the above-mentioned composition. The above-mentioned manufacturing method is a method capable of forming a coating containing zinc oxide without a binder, as opposed to a method of forming a coating containing zinc oxide using a coating liquid containing zinc oxide particles and a binder. In addition, according to the above-mentioned manufacturing method, it is also possible to firmly attach zinc oxide to the substrate surface, which is the surface to be coated. Furthermore, compared to a coating containing zinc oxide formed using zinc oxide particles and a binder, the coating formed by the above-mentioned manufacturing method is preferable from the viewpoint of exhibiting high heat resistance. In addition, as described above, the coating formed by the above-mentioned manufacturing method can contain iron oxide provided by a β-diketone metal compound represented by formula (2). The above-mentioned manufacturing method is suitable as a method for manufacturing the above-mentioned article.
[0056] The above-mentioned production method will now be described in more detail.
[0057] <Application of composition> The substrate to which the composition is applied is as described above. As a method for applying the gradual-seasoning composition, known methods such as droplet application, electrostatic application, spin application, and dip application can be used. The droplet application is preferred in terms of not being limited to the shape of the substrate. Specific examples of the droplet application include spray application and mist CVD (Chemical vapor deposition) methods. The spray application is a method in which the coating liquid is sprayed from a nozzle. As the spray application device, a commercially available spray application device and a spray application device of a known configuration can be used. The mist CVD method is a method in which the coating liquid is misted by an ultrasonic mist generator or the like, and the mist is supplied to the substrate surface. As the mist CVD application device, a commercially available mist CVD application device and a mist CVD application device of a known configuration can be used.
[0058] The composition can be applied in an atmosphere in which water and oxygen are present. The relative humidity of the "atmosphere in which water and oxygen are present" can be, for example, 20% or more and 100% or less. From the viewpoint of smooth formation of a coating, the relative humidity of the "atmosphere in which water and oxygen are present" is preferably 40% or more and 100% or less, and more preferably 50% or more and 100% or less, or 50% or more and 90% or less. The oxygen concentration in the "atmosphere in which water and oxygen are present" can be, for example, 5 vol.% to 50 vol.%, 10 vol.% to 40 vol.%, or 15 vol.% to 30 vol.%, with the total volume of gas in the atmosphere (excluding water vapor) being 100 vol.%. The "atmosphere in which water and oxygen are present" can be, for example, air, and preferably air containing water with a relative humidity in the above range. Alternatively, the "atmosphere in which water and oxygen are present" can be an atmosphere of a mixed gas of nitrogen, oxygen, and water instead of the air described above. As is well known, the oxygen concentration in air is about 20% by volume relative to the total amount of gas excluding water vapor. The composition can be applied, for example, under atmospheric pressure or under pressure, preferably under atmospheric pressure in the presence of water and oxygen. Applying the composition under atmospheric pressure is preferred because it is convenient in terms of the apparatus.
[0059] The composition can be applied to the substrate by heating the substrate. The substrate temperature during application can be, for example, less than 400° C., and the substrate temperature can be controlled by a known heating means such as a heater. In the present invention and this specification, the term "substrate temperature" refers to the temperature of the substrate surface on which the coating liquid (specifically, the composition) is applied. If necessary, the substrate temperature can be set to a predetermined temperature, and after drying the solvent, heating for forming zinc oxide can be performed at a predetermined temperature. It is also presumed that this heating can form an oxide containing iron atoms. It is also possible to make the solvent drying temperature and the substrate temperature for the subsequent zinc oxide formation the same, and to simultaneously perform solvent drying and zinc oxide formation. The substrate temperature can also be appropriately set, such as by increasing the temperature in multiple stages depending on the type of solvent contained in the coating liquid.
[0060] The temperature of the atmosphere in which the coating is performed can be, for example, 50°C or less. The coating of the composition is preferably performed at an atmospheric temperature of 50°C or less and a substrate temperature of less than 400°C. From the viewpoint of promoting the crystallization of zinc oxide in the coating, the atmospheric temperature in which the coating is performed is preferably 0°C or more and 40°C or less, and the substrate temperature is preferably 100°C or more and 250°C or less. Furthermore, the number of cycles of "coating-drying-heating" can be one or more than two. By repeating the cycle two or more times, the coating can be made thicker. In addition, various coating conditions such as the coating amount of the composition, the coating speed, the size of the droplets discharged from the spray nozzle when spray coating is performed, the distance between the substrate and the spray nozzle during coating, and the spray pressure can be set according to the concentration of the organozinc compound and the concentration of the β-diketone metal compound in the composition, the specifications of the coating device used, the thickness of the coating to be formed, and the like. EXAMPLES
[0061] The present invention will be described below based on examples, but the present invention is not limited to the embodiments shown in the examples.
[0062] The preparation of the following coating solutions was carried out in a nitrogen gas atmosphere, and all solvents were dehydrated before use.
[0063] [Examples 1 to 4, Comparative Example 4] As an organozinc compound represented by formula (1), diethylzinc (R 1 and R 2 is an ethyl group) was used as the β-diketone compound represented by formula (2), iron(III) acetylacetonate (M is an iron atom, R is an ethyl group) was used as the β-diketone compound represented by formula (2). 3 and R 4 is a methyl group). 0.3 g to 1.6 g of diethylzinc was added to 17.2 g of xylene, and then iron(III) acetylacetonate was added in an amount such that the percentage of the iron atoms relative to the total of the zinc atoms contained in the diethylzinc and the iron atoms contained in the iron(III) acetylacetonate would be the value shown in the "Amount Added" column in Table 1, and the mixture was thoroughly stirred to obtain a coating liquid (coating composition). The coating liquid obtained above was filled into a spray bottle of a spray coating device. As the spray coating device, a spray coating device (fixed nozzle type) described in JP 2011-170979 A was used. As the substrate, a glass substrate (EAGLEXG manufactured by Corning) having a size of 5 cm x 5 cm was placed on a substrate holder, and heated to a substrate temperature of 200°C. After that, the coating liquid was sprayed (spray coating) from the spray nozzle for 8 to 16 minutes in air containing water at atmospheric pressure, an ambient temperature of 25°C, and a relative humidity of 50%, with the coating liquid set to 1 ml / min and the carrier gas nitrogen set to 8 L / min. As the spray nozzle, an Atmax nozzle AM6 type manufactured by ATOMAX was used. The size of the droplets discharged from the spray nozzle was in the range of 3 to 20 μm, and spray coating was performed with the distance between the spray nozzle and the substrate set to 20 cm, to form a coating on the substrate.
[0064] [Example 5] 2.3 g of diethylzinc was added to 50 g of anisole, and then iron(III) acetylacetonate was added in an amount such that the percentage of the iron atoms relative to the total of the zinc atoms contained in the diethylzinc and the iron atoms contained in the iron(III) acetylacetonate would be the value shown in the "Amount Added" column in Table 1, and the mixture was thoroughly stirred to obtain a coating solution. As a spray coating device, rCoater (movable nozzle type) manufactured by Asahi Sunac Corporation was used. As a substrate, a glass substrate (EAGLEXG manufactured by Corning) measuring 5 cm x 5 cm was placed on a substrate holder and heated to a substrate temperature of 200°C. The coating solution was spray coated five times at a spray pressure of 0.12 MPa in air containing water at atmospheric pressure, an ambient temperature of 25°C, and a relative humidity of 50%. The size of the droplets discharged from the spray nozzle was in the range of 3 to 20 μm, and the distance between the spray nozzle and the substrate was 25 cm, and spray coating was performed to form a coating on the substrate.
[0065] [Example 6] The coating solution was prepared by the method described for Example 5. The prepared coating liquid was filled into a spray bottle of a spray coating device. As the spray coating device, a spray coating device (fixed nozzle type) described in JP 2011-170979 A was used. As the substrate, a glass substrate (EAGLEXG manufactured by Corning) having a size of 5 cm x 5 cm was placed on a substrate holder, and heated to a substrate temperature of 200°C. After that, the coating liquid was sprayed (spray coating) for 16 minutes from a spray nozzle at 1 ml / min and a carrier gas of nitrogen at 13 L / min in air containing water at atmospheric pressure, 25°C, and a relative humidity of 50%. As the spray nozzle, an Atmax nozzle AM6 manufactured by ATOMAX was used. The size of the droplets discharged from the spray nozzle was in the range of 3 to 20 μm, and spray coating was performed with the distance between the spray nozzle and the substrate being 23 cm, to form a coating on the substrate.
[0066] [Comparative Example 1] 7.2 g of diethylzinc alone was added to 86.0 g of xylene and thoroughly stirred to obtain a coating solution. The coating solution was sprayed on the substrate in the same manner as described in Example 5 to form a coating.
[0067] [Comparative Example 2] 1.8 g of diethylzinc was added to 43.0 g of xylene, and then ferrocene was added in an amount such that the percentage of the iron atoms relative to the total of the zinc atoms contained in the diethylzinc and the iron atoms contained in ferrocene was the value shown in the "Amount Added" column in Table 1, and the mixture was thoroughly stirred to obtain a coating solution. Ferrocene is a metal compound that does not fall under formula (2). The coating solution was spray-coated by the method described in Examples 1 to 4 to form a coating on the substrate.
[0068] [Comparative Example 3] 2.2 g of iron (III) acetylacetonate alone was added to 17.2 g of xylene and thoroughly stirred to obtain a coating solution. The coating solution was spray-coated by the method described in Examples 1 to 4 to form a coating on the substrate.
[0069] [Film thickness measurement] In the examples and comparative examples, the thickness of the coating formed on the substrate was measured using a stylus-type surface profiler (DektakXT-S manufactured by Bruker Nano).
[0070] [Transmittance measurement] In the examples and comparative examples, the transmission spectra of the coatings formed on the substrates were measured using a spectrophotometer manufactured by JASCO Corporation, and the visible light transmittance (average transmittance in the visible light region of 600 nm to 800 nm) and the transmittance at wavelengths of 350 nm and 420 nm were determined.
[0071] The transmission spectra measured for each of the examples and comparative examples are shown in FIGS.
[0072] The results are shown in Table 1. From the results shown in Table 1, the following (1) to (3) can be confirmed. (1) The coatings formed in Examples 1 to 6 are superior to the coatings formed in Comparative Examples 3 and 4 in blocking ultraviolet light with a wavelength of 350 nm. (2) The coatings formed in Examples 1 to 6 are superior to the coatings formed in Comparative Examples 1, 2, and 4 in blocking high-energy visible light with a wavelength of 420 nm. (3) The coatings formed in Examples 1 to 6 have high visible light transmittance.
[0073] As described above, it was confirmed that the coatings formed in Examples 1 to 6 exhibited excellent light-shielding function against light rays in a wide wavelength range (ultraviolet rays and high-energy visible light rays), and furthermore, were coatings with high visible light transmittance.
[0074] [Table 1]
[0075] [Measurement of iron content in coating] For each of Example 1, Example 2, Example 4, Comparative Example 1, and Comparative Example 4, a test piece of 10 mm x 10 mm in size was cut out from the glass substrate on which the coating was formed by the method described above, and placed in a vial, and the coating was eluted with 1.0 mL of nitric acid (1.38). The eluate was then washed into a 20 mL measuring flask with ultrapure water, and the volume was adjusted to a constant value to obtain an ICP measurement solution. The ICP measurement solution was quantitatively analyzed using an ICP-AES method (ICP emission analyzer: OPTTIMA7300DV manufactured by PerkinElmer). A blank was set for the analysis, and all analysis results were corrected. The quantitative analysis results are shown in Table 2, and a graph plotted against the percentage of iron atoms in the coating solution (coating composition) is shown in FIG. 11. In Table 2, "at%" indicates "atomic %". "Solution (Fe, at%)" is the percentage of iron atoms in the coating solution (coating composition), and "film Fe" is the iron content of the coating. From the results shown in Table 2 and FIG. 11, it can be confirmed that the percentage of iron atoms in the coating liquid (coating composition) and the iron content in the coating correspond well.
[0076] [Table 2]
[0077] [Evaluation of film properties (Example 6)] <Evaluation of film properties (1)> Figure 12 shows a grayscale image (256 gradations) and brightness analysis results of a cross-sectional STEM image of the entire thickness direction of a randomly selected portion of the coating formed in Example 6. The brightness analysis was performed using the free software ImageJ as image processing software. Figure 12 shows a part of the brightness analysis results of low brightness areas and high brightness areas.
[0078] Table 3 shows the maximum and minimum arithmetic average brightness values of the low brightness regions and the maximum and minimum arithmetic average brightness values of the high brightness regions observed in the cross-sectional STEM image shown in FIG.
[0079] [Table 3]
[0080] <Evaluation of film properties (2) and (3)> FIG. 13 shows the results of cross-sectional observation by STEM-EDX and the results of EDX intensity analysis of the entire thickness direction of a randomly selected portion of the coating formed in Example 6. The EDX intensity analysis was performed by line analysis. FIG. 13 shows a part of the EDX intensity analysis results of low brightness regions and high brightness regions. The minimum value of the EDX intensity ratio (Zn / Fe) among the multiple low brightness regions was higher than the maximum value of the EDX intensity ratio (Zn / Fe) among the multiple high brightness regions. The ratio "EDX low brightness region / EDX high brightness region" was 2.489 / 1.236 = approximately 2.0.
[0081] [Evaluation of film properties (Example 1)] <Evaluation of film properties (1)> 15 shows a grayscale image (256 gradations) and brightness analysis results of a cross-sectional STEM image of the entire thickness direction of a randomly selected portion of the coating formed in Example 1. The brightness analysis was performed using the free software ImageJ as image processing software.
[0082] Table 4 shows the maximum and minimum arithmetic averages of the brightness values of the low brightness regions and the arithmetic averages of the brightness values of the high brightness regions observed in the cross-sectional STEM image shown in FIG.
[0083] [Table 4]
[0084] <Evaluation of film properties (2) and (3)> FIG. 16 shows the results of cross-sectional observation by STEM-EDX and the results of EDX intensity analysis of the entire thickness direction of a randomly selected portion of the coating formed in Example 1. The EDX intensity analysis was performed by line analysis. The minimum value of the EDX intensity ratio (Zn / Fe) in the two low brightness regions was higher than the EDX intensity ratio (Zn / Fe) in the high brightness region. The ratio "EDX low brightness region / EDX high brightness region" was 15.310 / 2.275=about 6.7.
[0085] In the above evaluation, a JEM-2010MX manufactured by JEOL was used as the transmission electron microscope, and an EM-Z02210T JEC manufactured by JEOL was used as the EDX. The observation conditions were as described above, and the brightness was manually adjusted to a brightness that was easy to see.
[0086] From the above results, it can be confirmed that the coating formed in Example 1 and the coating formed in Example 6 satisfy the film properties (1) to (3). Furthermore, since the transmission spectra of the coatings formed in Examples 2 to 5 (FIGS. 2 to 5) have spectral shapes similar to the transmission spectrum of the coating formed in Example 1 (FIG. 1) and the transmission spectrum of the coating formed in Example 6 (FIG. 6), it can be confirmed that the coatings formed in Examples 2 to 5 also satisfy the film properties (1) to (3) like the coating formed in Example 1 and the coating formed in Example 6. Furthermore, the coating liquid used in Example 6 has the same percentage of iron atoms as the coating liquid used in Example 2. Therefore, the iron content of the coating formed in Example 6 is similar to the iron content of the coating formed in Example 2 shown in Table 2. Therefore, the coating formed in Example 6 also satisfies the film physical property (4). This point is also the same for the coating formed in Example 5. Moreover, the percentage of iron atoms in the coating liquid used in Example 3 (60 atomic %) exceeds the percentage of iron atoms in the coating liquid used in Example 2 (40 atomic %) and is less than the percentage of iron atoms in the coating liquid used in Example 4 (80 atomic %). Therefore, the iron content of the coating formed in Example 6 exceeds the value of Example 2 shown in Table 2 and is less than the value of Example 4, so that the coating formed in Example 3 also satisfies the film property (4). As described above, the coatings formed in Examples 1 to 6 are coatings that satisfy the film properties (1) to (4).
[0087] [Thickness of each region and total number of layers] 14 shows the film thickness (unit: nm) and the total number of layers for low-brightness and high-brightness regions in a grayscale image (256 gradations) of a cross-sectional STEM image of the entire thickness direction of a randomly selected portion of the coating formed in Example 6. The total number of layers in the low-brightness regions was 9 layers, and the total number of layers in the high-brightness regions was 8 layers. 17 shows the film thickness (unit: nm) and the total number of layers for low-brightness and high-brightness regions in a grayscale image (256 gradations) of a cross-sectional STEM image of the entire thickness direction of a randomly selected portion of the coating formed in Example 1. The total number of layers in the low-brightness regions was two, and the total number of layers in the high-brightness regions was one. The above film thickness analysis was carried out using the free software ImageJ as image processing software. [Industrial Applicability]
[0088] An embodiment of the present invention is useful in various technical fields in which it is desirable to block light in a wide wavelength range (ultraviolet rays and high-energy visible light).
Claims
1. An article having a coating on a substrate, the coating satisfying the following (1) to (4): (1) In the grayscale image of the cross-sectional STEM image, a layered structure in which low brightness regions and high brightness regions are alternately stacked is confirmed. (2) In cross-sectional observation using STEM-EDX, oxygen, zinc, and iron were detected. (3) In cross-sectional observation by STEM-EDX, the EDX intensity ratio of iron to zinc (Zn / Fe) in the region observed as the low brightness region is higher than the EDX intensity ratio (Zn / Fe) in the region observed as the high brightness region. (4) The percentage of the iron atoms relative to the total of the zinc atoms and iron atoms contained in the coating is more than 0.4 atomic %.
2. 2. The article according to claim 1, wherein the film thickness of the low luminance region is in the range of 5.0 nm or more and 250.0 nm or less, and the film thickness of the high luminance region is in the range of 5.0 nm or more and 250.0 nm or less.
3. The article according to claim 1 , wherein in the laminated structure, the total number of layers in the low luminance region is 1 to 15 layers, and the total number of layers in the high luminance region is 1 to 15 layers.
4. The article according to claim 1 , wherein in the laminated structure, the total number of layers in the low luminance region is 5 to 15, and the total number of layers in the high luminance region is 5 to 15.
5. The transmittance characteristics of the coating are The average transmittance in the wavelength range of 600 nm to 800 nm is 75.0% or more, The transmittance at a wavelength of 350 nm is 6.0% or less, and 2. The article according to claim 1, having a transmittance of 80.0% or less at a wavelength of 420 nm.
6. The film thickness of the low brightness region is in the range of 5.0 nm to 250.0 nm, The film thickness of the high brightness region is 5.0 nm or more and 250.0 nm or less, In the laminated structure, the total number of layers in the low-luminance region is 1 to 15 layers, and the total number of layers in the high-luminance region is 1 to 15 layers, The transmittance characteristics of the coating are The average transmittance in the wavelength range of 600 nm to 800 nm is 75.0% or more, The transmittance at a wavelength of 350 nm is 6.0% or less, and 2. The article according to claim 1, having a transmittance of 80.0% or less at a wavelength of 420 nm.
7. The article according to claim 6 , wherein in the laminated structure, the total number of layers in the low luminance region is 5 to 15, and the total number of layers in the high luminance region is 5 to 15.
8. The following formula (1): Formula (1): R 1 -Zn-R 2 (In formula (1), R 1 and R 2 each independently represents a linear or branched alkyl group having 1 to 8 carbon atoms. and an organozinc compound represented by the formula: The following formula (2): 【Chemistry 1】 (In formula (2), R 3 and R 4 each independently represents a linear or branched alkyl group having 1 to 8 carbon atoms. A β-diketone metal compound represented by the formula: and A composition in which the content of the β-diketone metal compound is more than 10 atomic %, expressed as a percentage of the iron atoms relative to the total of the zinc atoms contained in the organozinc compound and the iron atoms contained in the β-diketone metal compound.
9. In formula (2), R 3 and R 4 The composition according to claim 8 , wherein each of the formulas represents a methyl group.
10. The composition according to claim 8, wherein the content of the β-diketone metal compound is more than 10 atomic % and not more than 80 atomic %, expressed as a percentage of the iron atoms relative to the total of the zinc atoms contained in the organozinc compound and the iron atoms contained in the β-diketone metal compound.
11. The composition of claim 8 further comprising an organic solvent.
12. The composition according to claim 11, wherein the organic solvent is one or more organic solvents selected from the group consisting of aromatic hydrocarbon solvents and aromatic electron donating solvents.
13. In formula (2), R 3 and R 4 Each of these represents a methyl group. the content of the β-diketone metal compound is, as a percentage of the iron atoms to the total of the zinc atoms contained in the organozinc compound and the iron atoms contained in the β-diketone metal compound, more than 10 atomic % and 80 atomic % or less; 9. The composition of claim 8, further comprising one or more organic solvents selected from the group consisting of aromatic hydrocarbon solvents and aromatic electron donor solvents.
14. A method for producing an article having a coating on a substrate, the method comprising applying the composition according to any one of claims 8 to 13 onto the substrate.
Citation Information
Patent Citations
Production of artificial stone
JP1977088464A
Transparent conducting film forming composition and transparent conducting film forming method
JP1995182939A
Ultraviolet ray shielding film
JP2014205811A
Glass container
JP2019147695A
Composition for thin film formation of zinc oxide and method for producing zinc oxide thin film
JP2019152702A
